Identification and Prioritization of Factors Affecting the Cultural Model of Good Governance in Bodies Overseeing Government Performance Using Fuzzy ANP Method - Mohammadi, Heydar; Korang beheshti, Siamak; Davazdah-Emami, Hamid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The aim of the current research is to identify the effective factors on the cultural model of good governance in government performance monitoring agencies using the Fuzzy ANP method. Methodology: This research is considered applied in terms of its goal and is of a mixed nature. The research population, in a qualitative framework, consists of academic experts and specialists in government performance monitoring agencies, of which 10 individuals were selected through purposive judgment sampling. The data collection tool in this research is the Delphi questionnaire. Findings: The main factors affecting good cultural governance were identified based on the research background and expert opinions, based on structure, law, and value, and a total of 11 sub-criteria were also determined for the main factors. Conclusion: The results of the research indicate that the legal dimension was the most significant factor affecting the cultural model of good governance in government performance monitoring agencies, followed by value and structural factors in subsequent ranks. The main reasons affecting good governance based on culture relate to professional ethics, the suitability of culture with requirements, and the presence of a value system. In this regard, the enumeration of ethical principles in the organization and their institutionalization can be effective.